An All-Optical Frequency Up/Down-Converter Utilizing Stimulated Brillouin Scattering In A Trf And Dcf For Rof Application - Awang, N. A.; Ahmad, H.; Norizan, S. F.; Zulkifli, M.Z.; Ghani, Z.A.; Harun, S. W. (Journal of Science and Technology, 2010)
A frequency up and down conversion is proposed based on stimulated Brillouin scattering (SBS) for Radio-over-fiber (RoF) system. Microwave frequency up conversion from 2GHz to 12.5GHz and microwave frequency down conversion from 12.5GHz to 1.8GHz with largest Intermediate Frequency (IF) power of -32dBm is successfully demonstrated. The up conversion is based on the 1st Stokes of Brillouin fiber laser in Truewave reach fiber (TWF) and the down conversion is based on 1st AntiStokes of Brillouin fiber laser in Dispersion compensating fiber (DCF).